Speech Production and Possibilities of its Correction of Incoming Students Specialized in Media (Training and Practice : Journal of Educational Sciences, 2015)
Students specialized in media are also trained at the University of West Hungary. Elocution and speech-technique have significant role in their subjects. The work done during the lessons always depends on the team’s efficiency and the quality of their speech production. The speech production of the students differs during the various years of study – not only by the norms of the press-language but often by the norms of the standard language. This also includes creative writing skills, sentence formation and pronunciation. The most striking mistakes and problems are difficulties of articulation, nasality, deviant rhythm from norm, improper pronunciation of sibilants (sz-z-c-zs-cs), burring and dysphonia. In this study I would like to outline the status of the use of language and the communicative competence of the students.